Declining Colectomy Rates for Nonmalignant Colorectal Polyps in a Large, Ethnically Diverse, Community-Based Population. Issue 5 (28th May 2022) - Alam, Asim; Ma, Christopher; Jiang, Sheng-Fang; Jensen, Christopher D.; Webb, Kenneth H.; Boparai, Eshandeep S.; Jue, Terry L.; Munroe, Craig A.; Gupta, Suraj; Fox, Jeffrey; Hamerski, Christopher M.; Velayos, Fernando S.; et al.
Abstract : INTRODUCTION: Despite studies showing improved safety, efficacy, and cost-effectiveness of endoscopic resection for nonmalignant colorectal polyps, colectomy rates for nonmalignant colorectal polyps have been increasing in the United States and Europe. Given this alarming trend, we aimed to investigate whether colectomy rates for nonmalignant colorectal polyps are increasing or declining in a large, integrated, community-based healthcare system with access to advanced endoscopic resection procedures. METHODS: We identified all individuals aged 50–85 years who underwent a colonoscopy between 2008 and 2018 and were diagnosed with a nonmalignant colorectal polyp(s) at the Kaiser Permanente Northern California integrated healthcare system. Among these individuals, we identified those who underwent a colectomy for nonmalignant colorectal polyps within 12 months after the colonoscopy. We calculated annual colectomy rates for nonmalignant colorectal polyps and stratified rates by age, sex, and race and ethnicity. Changes in rates over time were tested by the Cochran-Armitage test for a linear trend. RESULTS: Among 229, 730 patients who were diagnosed with nonmalignant colorectal polyps between 2008 and 2018, 1, 611 patients underwent a colectomy. Colectomy rates for nonmalignant colorectal polyps decreased significantly from 125 per 10, 000 patients with nonmalignant polyps in 2008 to 12 per 10, 000 patients with nonmalignant polyps in 2018 ( P < 0.001 for trend). When stratified by age, sex, and race and ethnicity, colectomy rates for nonmalignant colorectal polyps also significantly declined from 2008 to 2018. DISCUSSION: In a large, ethnically diverse, community-based population in the United States, we found that colectomy rates for nonmalignant colorectal polyps declined significantly over the past decade likely because of the establishment of advanced endoscopy centers, improved care coordination, and an organized colorectal cancer screening program.